Ascending aortic aneurysm haemodynamics are associated with aortic wall biomechanical properties. (29th October 2021) - McClarty, Davis; Ouzounian, Maral; Tang, Mingyi; Eliathamby, Daniella; Romero, David; Nguyen, Elsie; Simmons, Craig A; Amon, Cristina; Chung, Jennifer Chia-Ying
Abstract:  : OBJECTIVES: The effect of aortic haemodynamics on arterial wall properties in ascending thoracic aortic aneurysms (ATAAs) is not well understood. We aim to delineate the relationship between shear forces along the aortic wall and loco-regional biomechanical properties associated with the risk of aortic dissection. METHODS: Five patients with ATAA underwent preoperative magnetic resonance angiogram and four-dimensional magnetic resonance imaging. From these scans, haemodynamic models were constructed to estimate maximum wall shear stress (WSS), maximum time-averaged WSS, average oscillating shear index and average relative residence time. Fourteen resected aortic samples from these patients underwent bi-axial tensile testing to determine energy loss ( Δ UL ) and elastic modulus (E 10 ) in the longitudinal (Δ U L long,   E 10 long ) and circumferential (Δ U L circ,   E 10 circ )   directions and the anisotropic index (AI )   for each parameter. Nine resected aortic samples underwent peel testing to determine the delamination strength (S d ) . Haemodynamic indices were then correlated to the biomechanical properties. RESULTS: A positive correlation was found between maximum WSS and Δ U L long   r s = 0.75,   P   =   0.002 and A I Δ UL (r s = 0.68,   P = 0.01 ) . Increasing maximum time-averaged WSS was found to be associated with increasing Δ U L long (r s = 0.73,   P   =   0.003 ) and A I Δ UL (r s = 0.62,   P = 0.02 ) .   Average oscillating shear index positively correlated with S d (r s = 0.73, P = 0.04 ) . No significant relationship was found between any haemodynamic index and E 10, or between relative residence time and any biomechanical property. CONCLUSIONS: Shear forces at the wall of ATAAs are associated with local degradation of arterial wall viscoelastic hysteresis (Δ UL ) and delamination strength, a surrogate for aortic dissection. Haemodynamic indices may provide insights into aortic wall integrity, ultimately leading to novel metrics for assessing risks associated with ATAAs. Abstract : Ascending thoracic aortic aneurysms (ATAAs) affect 10/100 000 persons per year and are associated with an increased risk of aortic dissection or rupture [1].